The role of municipal public accounts committee in enhancing accountability and municipal performance in Fetakgomo Tubatse Local Municipality - Seerane, Marumo Moses (My University, 2023)
This mixed-methods case study examined the role of the Municipal Public Finance Committee (MPAC) in enhancing accountability and municipal performance in Fetakgomo Tubatse Local Municipality. The primary objective of this study was to gain insight into the establishment of MPACs and the state of accountability and performance in the municipality and the effectiveness with which MPACs are able to enhance accountability by municipal officials. Purposive and convenience sampling strategies were used to select eight MPAC members and fifteen councillors from whom qualitative and quantitative research data were collected using anonymised semi-structured questionnaires. Findings indicate that MPACs are adequately established in the municipality and play a critical role in ensuring oversight of municipal council compliance with requisite public finance guidelines in the delivery of services and ensuring that the municipal council adopts and implements resolutions made by the MPAC and Auditor-General. However, MPAC's independence, skill capacity and staffing shortages, as well as the culture of unaccountability and subtle reluctance on the part of the municipal council to uphold and implement its recommendations are major challenges that thwart MPAC's role in ensuring accountability and municipal performance. These findings contribute to the knowledge gaps related to the establishment, roles, challenges, and effectiveness of MPACs in conducting internal oversight activities in local municipalities.
Thesis (MPAM.) -- University of Limpopo, 2023
Keywords: Role; Municipal public accounts committee; Accountability; Municipal performance; Fetakgomo-Tubatse Local Municipality; Fetakgomo-Tubatse Local Municipality -- South Africa; Government accountability -- South Africa -- Limpopo Province; Municipal finance -- South Africa -- Limpopo